INCREASING LABOR EFFICIENCY IN THE AREA OF DIGITAL ENTREPRENEURSHIP - Potekhina, Elena; Gulina, Irina; Dmitrieva, Olga; Frolova, Victoria; Semenova, Julia (Revista Inclusiones, 2020)
The article deals with the organizational and economic aspects of improving labor efficiency in the area of digital entrepreneurship. It is established that the mass spread of digital technologies contributes to the formation of network relations and the emergence of information networks based on the interaction of individual members of society. It is revealed that the increase in information pressure on the entrepreneur through new technologies makes the traditional algorithms for obtaining information and processing it insufficiently effective. The authors have proved that the creation of programs, training, and continuous improvement of the level of digital competencies of entrepreneurs are an urgent need for economic development at the present stage, and have revealed that the formation of professionally competent personnel allows improving the quality of work performed, and ensuring high labor efficiency in a competitive environment. This can be done using techniques and methods, such as state programs for the dissemination of digital competencies, restructuring the education system, creating training platforms, and encouraging the acquisition of digital competencies at the microlevel.